1956
DOI: 10.3181/00379727-91-22199
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Radioactive Para-Aminobenzoic Acid in an Escherichia coli Mutant.

Abstract: While metabolism of para-aminobenzoate (P-AB) has been extensively investigated in the mammalian body( 1,2), its function and biochemical transformations in microorganisms are still obscure. Conversion of PAB into folic acid and the citrovorum factor occurs in some organisms (3,4) a1 though there is some question whether these are the active forms of PAB. A number of other routes of metabolism have been reported. Davis( 5 ,6 ) has implicated PAB in the metabolism by Escherichia C O Z~ of tryptophane, tyrosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1957
1957
1961
1961

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
(2 reference statements)
0
1
0
Order By: Relevance
“…Other workers have found that leucovorin is a stable form of metabolically active folic acid when cells or cellular homogenates are either grown or incubated with p-aminobenzoic or pteroylglutamic acid. Reid and Couch (1955) found that chicken liver homogenates converted pteroylglutamic acid to leucovorin; Nichol (1954) reported that cellfree extracts of S. faecalis converted pteroylglutamic acid to leucovorin; Laseelles and Woods (1954) reported that suspensions of S. faecalis strain ATCC 8043 incubated with pteroylglutamic acid produce leucovorin; Davidson et al (1956) fed radioactive p-aminobenzoic acid to a p-aminobenzoic acid-requiring mutant of E. coli and isolated radioactive compounds which seemed to resemble leucovorin.…”
Section: Resultsmentioning
confidence: 99%
“…Other workers have found that leucovorin is a stable form of metabolically active folic acid when cells or cellular homogenates are either grown or incubated with p-aminobenzoic or pteroylglutamic acid. Reid and Couch (1955) found that chicken liver homogenates converted pteroylglutamic acid to leucovorin; Nichol (1954) reported that cellfree extracts of S. faecalis converted pteroylglutamic acid to leucovorin; Laseelles and Woods (1954) reported that suspensions of S. faecalis strain ATCC 8043 incubated with pteroylglutamic acid produce leucovorin; Davidson et al (1956) fed radioactive p-aminobenzoic acid to a p-aminobenzoic acid-requiring mutant of E. coli and isolated radioactive compounds which seemed to resemble leucovorin.…”
Section: Resultsmentioning
confidence: 99%